Complex evolutionary relationships in Origanum section Majorana (Lamiaceae). (19th March 2013) - Lukas, Brigitte; Samuel, Rosabelle; Mader, Eduard; Başer, Kemal Hüsnü Can; Duman, Hayri; Novak, Johannes
<x xml:space="preserve">Abstract</x> Origanum (Lamiaceae) comprises a number of essential oil‐rich species that have been used by humans for centuries. Today, the four species of section Majorana (O. onites, O. dubium, O. majorana and O. syriacum) are amongst the most widely used. Despite the importance of this section, phylogenetic relationships and species boundaries amongst its four taxa are unclear. In the present investigation, we used DNA sequence data from two nuclear regions [internal transcribed spacer (ITS) and 1‐deoxy‐d‐xylulose 5‐phosphate synthase (DXS)] as well as five microsatellite loci to test the taxonomic status of the four species of section Majorana. The combined DNA data revealed O. onites and O. syriacum as the older species in the section. Origanum majorana descends directly from O. syriacum. Origanum dubium was found to be of hybridogenous origin showing attributes of O. onites, O. syriacum and a third, unknown, Origanum species. Both sequence and microsatellite analyses provided evidence for recent hybridization between O. onites and O. dubium in Turkey. © 2013 The Linnean Society of London, <mixed-citation id="boj12022-cit-0077" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"><source content-type="journalTitle">Botanical Journal of the Linnean Society</source>, <year>2013</year>, <volume>171</volume>, <fpage>667</fpage>–<lpage>686</lpage>.</mixed-citation>